In the Shadow of War: The Journal of Palestine Studies as Archive. Issue 2 (11th May 2022) - Seikaly, Sherene
Abstract: In this article, coeditor Sherene Seikaly examines the Journal of Palestine Studies ' first two decades as the premier English-language academic publication on the Palestinian question and what was once referred to as the Arab-Israeli conflict. Using the keyword "war" in article titles as a prism for a granular analysis of the knowledge produced in the Journal, Seikaly traces some of the trends that undergirded JPS 's evolution—its prescriptive, programmatic, and prognosticating approach that was deeply imbricated in the patriarchal paradigms of international relations and political science (Revolution with a capital "R, " the "great men" of history, the imperative to make one's case before the colonizer), but also a capacious space to view the contested terrain of knowledge production. A close reading of seventeen articles and one interview over the arc of twenty years illuminates the Journal 's pivotal role as a repository of primary and secondary literature and as an archive of Palestine and the Palestinians.